Knowledge and practice in English medicine, 1550-1680 - Wear, A. (Andrew), 1946- (Cambridge University Press, 2000)
This is a major synthesis of the knowledge and practice of early modern English medicine set in its social and cultural contexts. The book vividly maps out some central areas such as remedies (and how they were made credible) and how and why surgeons worked upon the body.